Promotion of Learning Foreign Languages in Educational Institutions - Jo’rayeva Yulduz Rozikulovna (Scientific Trends, 2023)
This article provides detailed information on efforts to popularize foreign language learning in educational institutions. In addition, it was discussed that learning foreign languages is not only a means of communication, but also a door to many opportunities, and the importance of learning different languages in human life.
Keywords: Foreign languages; rating; content; international recruitment.